Business Strategies and Digital Marketing Management in Desa Prima Sleman SMEs - Istanto, Yuni; Sugandini, Dyah; Nusanto, Gunawan; Pamuji, Windy Anindya; Ekawati, Trestina (RSF Conference Series: Business, Management and Social Sciences, 2021)
This review expects to give knowledge to SMEs in Sleman regarding how organizations seeking different techniques approach this advanced promoting issue. A definitive objective is to help SMEs in Sleman in the productive and viable execution of the system embraced by their organizations. The technology provided to SMEs planned in this research is a digital technology for product marketing and improving product quality and production. The population in this study were all SME's in Sleman. The census did sampling. The research approach is made by survey, observation, FGD, and in-depth interview. The overall hypothesis in this study is positively and significantly supported. The research that has been done shows that SMEs in Sleman have a marketing performance that is influenced by the types of digital marketing strategies and strategies. On the other hand, the performance of SMEs is influenced by marketing performance.